2017
DOI: 10.1007/s12272-017-0920-3
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan-extending and stress resistance properties of brazilin from Caesalpinia sappan in Caenorhabditis elegans

Abstract: This study contributes to the continual discovery of lifespan-extending compounds from plants, using the Caenorhabditis elegans model system. An ethyl acetate soluble fraction of methanol extract from the heartwood of Caesalpinia sappan showed a significant lifespan-extending activity. Subsequent activity-guided chromatography of the ethyl acetate-soluble fraction led to the isolation of brazilin. Brazilin showed potent 2,2-diphenyl-1-picrylhydrazyl radical scavenging and superoxide anion quenching activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The nematodes were collected in M9 buffer and washed three times. Then, they were resuspended in M9 buffer and homogenized in ice (Lee, Xing & Kim, 2017). SOD activity was measured according to a SOD activity detection kit by using Multimode Plate Reader (Infinite F200 PRO, Tecan, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…The nematodes were collected in M9 buffer and washed three times. Then, they were resuspended in M9 buffer and homogenized in ice (Lee, Xing & Kim, 2017). SOD activity was measured according to a SOD activity detection kit by using Multimode Plate Reader (Infinite F200 PRO, Tecan, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…There are further examples of age-at-measurement effects, with other phenotypes such as locomotion and the level of ROS. The locomotion in young nematodes (age A1-A4) did not benefit from treatments with 50 lM brazilin (Lee et al 2017), 50 lg/mL dichloroacetate (Schaffer et al 2011), 0.24 g/mL Glycyrrhizae radix extract (Ruan et al 2016), 10 lM icariside II (Cai et al 2011), or 100 lM protocatechuic acid (Kim et al 2014), but the beneficial effects of these treatments were visible at older ages (A8, A8-A21, A12, A10, or A8, respectively). Similar observations were also reported in locomotion measurements using 50 lM or 100 lM piceatannol (Shen et al 2017), 25 lM silymarin (Kumar et al 2015), 25 lM tomatidine (Fang et al 2017), and 200 mg/mL blueberry extract (Wang et al 2018), showing positive effect of the treatments only in aged nematodes.…”
Section: Age At Compound Exposure and Phenotypic Measurements Mattersmentioning
confidence: 99%
“…Previous studies have shown that the majority of the beneficial pharmaceutical effects exerted by brazilin are concerned with its regulation on oxidative stress (14)(15)(16)(17)(18)(19). For example, Wang et al (14) suggested that brazilin exerted antidepressant-and anxiolytic-like effects in mice with chronically mild stress (CMS)-induced depression, probably through inhibiting oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Brazilin, a homoisoflavonoid (C 16 H 14 O 5 ; chemical structure shown in Figure 1A), is a natural product of Caesalpinia sappan L. and it has been widely used as a traditional medicine for a long time in history (13). Brazilin has been reported to possess multiple pharmaceutical effects, including its efficacy in treating depressive and anxiety disorders (14), ameliorating oxidative stress-induced photoaging of skin (15), protecting auditory cells against t-butyl hydroperoxide (t-BHP)-induced cell death (16,17), suppressing high glucose-induced vascular inflammatory processes (18), extending lifespan in C. elegans (19) and so on. These effects are predominantly based on its powerful antioxidant activity, as evidenced by the fact that brazilin has been shown to inhibit antioxidant enzyme gene expression (16,17), lower the accumulation of intracellular ROS (18,19), and increase superoxide dismutase (SOD) activity (19).…”
Section: Introductionmentioning
confidence: 99%